2021
DOI: 10.1002/hep4.1665
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bile Acid, Vitamin E, and Serotonin Metabolites Are Associated With Future Liver‐Related Events in Nonalcoholic Fatty Liver Disease

Abstract: Identifying patients at higher risk for poor outcomes from nonalcoholic fatty liver disease (NAFLD) remains challenging. Metabolomics, the comprehensive measurement of small molecules in biological samples, has the potential to reveal novel noninvasive biomarkers. The aim of this study was to determine if serum metabolite profiles in patients with NAFLD associate with future liver‐related events. We performed a retrospective single‐center cohort study of 187 participants with biopsy‐proven NAFLD. Metabolomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…In NAFLD patients increased levels of 5-HIAA, the serotonin marker commonly used to screen for neuroendocrine tumors, were correlated with an increased risk for liver related complications such as ascites and hepatocellular carcinoma [88].…”
Section: Serotonin and Melatonin Pathwaysmentioning
confidence: 99%
“…In NAFLD patients increased levels of 5-HIAA, the serotonin marker commonly used to screen for neuroendocrine tumors, were correlated with an increased risk for liver related complications such as ascites and hepatocellular carcinoma [88].…”
Section: Serotonin and Melatonin Pathwaysmentioning
confidence: 99%
“…A previous retrospective single-center cohort study, which included 187 participants, reported that vitamin E, primary bile acid and serotonin are associated with occurrence of future liver-related events [ 141 ]. A double blind randomized, and placebo-controlled trial was conducted previously whereby patients received three infusions containing vitamin E and the results showed significant improvement for ALT, AST and lactate dehydrogenase (LDH) levels after surgery [ 142 ].…”
Section: Metabolic Compartmentmentioning
confidence: 99%
“…[5,40] In the recent decade, extensive studies from animal models and human patients have found that NAFLD disease progression is closely associated with bile acid dysregulation and sphingolipid homeostasis. [48][49][50][51][52][53][54][55][56][57][58][59][60] Mechanisms linking bile acid metabolism to the development of NAFLD Consistently, clinical studies have demonstrated that primary and secondary CBAs are tightly associated with NAFLD progression and NASH severity. [30,48,49,51,52] A recent study reported that elevated hepatic taurochenodeoxycholic acid (TCDCA) and taurocholic acid (TCA) in NAFLD patients was associated with symptom onset, disease progression, or death.…”
Section: Bile Acids and Sphingolipids In Nafldmentioning
confidence: 99%